The trade union freedom of foreigners with no authorization to work - Roales-Nieto, Consuelo Nieto; Pereira, Ricardo José Macedo de Britto (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The need of working, intended in its most primitive expression, as a mean for subsistence, is one of the fundamental causes for the increasement of migratory movements. As a result, a peculiar situation arises: there are foreign workers to whom the law that regulates the right to work does not apply.As trade union freedom is one of the fundamental rights related to work, it does not apply either. The article analyses the compatibility of the dispositions about foreigners that, in this respect, condition the exercise of the freedom of syndication, to the authorization of permanence in the country or residence permission with the scope of application of trade union freedom right provided by the Spanish Bill of Rights. The study does not try to establish the practical viability of the possibility for a foreigner to be covered by the right of syndication but the legitimacy of the normative implications when foreigner´s law (Ley de extranjería) is applied confronted to the principles stated in the Spanish Constitution and in international treaties.